Minat Wisatawan Terhadap Produk Ampalang Ikan Pipih Khas Kalimantan Timur - Anitra, Vera; Cholid, Idham (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2019)
The specific purpose of this study was to determine the extent to which tourists' buying interest in East Kalimantan's specialty is especially the food product of flat fish. The general purpose of this study is to improve the work of human resources in processing typical products of East Kalimantan in improving the economy. The analytical technique used was the Stuctural Equation Model (SEM) with AMOS 21. The data were taken from questionnaires distributed to tourists who were shopping for typical East Kalimantan products in the cities of Samarinda, Balikpapan and Bontang. The results showed that the variables of interest had a negative and insignificant ef ect on the economy, it could be concluded that the price of ered did not become an obstacle for tourists to buy the product. The results of this study indicate that the type of product, demography, psychology has a positive ef ect on tourist buying interest.